(untitled) (Research, Society and Development, 2022)
Objective: To identify the main nursing care related to the prevention of prolapse in intestinal ostomies. Methodology: This is an integrative review, using the databases of Literatura Latino-americana e do Caribe em Ciências da Saúde (LILACS), Scientific Electronic Library Online (SciELO), Base de Dados de Enfermagem (BDENF), Medical Literature Analysis and Retrieval System On-line (PubMed/MedLine) and Cumulative Index to Nursing and Allied Health Literature (CINAHL), in Portuguese, English and Spanish, published between 2011 and 2020. After searching the scientific literature, twenty-two studies were selected for analysis on the care related to the prevention of prolapse. Results: The demarcation of the stoma, preoperative education, educational telephone follow-up of post-discharge support carried out by the stomatherapist were appointed as care and/or strategies for preventing prolapse. Conclusion: Previous surgical demarcation of the stoma associated with preoperative education and education and/or intervention programs aimed at postoperative ostomy management can be considered important care technologies capable of preventing prolapse in intestinal ostomies. However, the realization of demarcation still lacks more robust scientific evidence, considering that its practice is still not carried out, on a large scale, in the international scope.